2017
DOI: 10.1088/1741-4326/aa57d9
|View full text |Cite
|
Sign up to set email alerts
|

Runaway electron generation during disruptions in the J-TEXT tokamak

Abstract: A systematic study of disruption-generated runaway electrons has been performed in the J-TEXT tokamak. During the intended disruption by the argon injection in J-TEXT, the runaway electron plateau is more easily obtained with a higher loop voltage and shorter onset time of high loop voltage. Magnetic fluctuations are observed at the beginning of the current quench during the disruptions. The generated runaway electron (RE) current is larger at a lower level of magnetic fluctuation. Experimental evidence suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 40 publications
2
38
0
1
Order By: Relevance
“…Some qualitative trends in RE seed formation can be inferred from RE plateau current JT-60U, ASDEX-U, and JET have observed data supporting a B ∼ 2 T toroidal field threshold for RE seed formation [206,235,243], leading to speculation that excitation of whistler waves could prevent RE formation below B = 2 T [158]. However, later experiments in JET [244], KSTAR [245], TEXTOR [246], and J-TEXT [247] found that there is no clear toroidal field threshold, so that B = 2 T is not a prerequisite for RE formation. Nevertheless, a robust trend is observed across all machines that higher toroidal magnetic field does elevate the RE plateau levels.…”
Section: E Re Seed Formation During Tqmentioning
confidence: 99%
“…Some qualitative trends in RE seed formation can be inferred from RE plateau current JT-60U, ASDEX-U, and JET have observed data supporting a B ∼ 2 T toroidal field threshold for RE seed formation [206,235,243], leading to speculation that excitation of whistler waves could prevent RE formation below B = 2 T [158]. However, later experiments in JET [244], KSTAR [245], TEXTOR [246], and J-TEXT [247] found that there is no clear toroidal field threshold, so that B = 2 T is not a prerequisite for RE formation. Nevertheless, a robust trend is observed across all machines that higher toroidal magnetic field does elevate the RE plateau levels.…”
Section: E Re Seed Formation During Tqmentioning
confidence: 99%
“…Significant work has been done to prevent REs in ITER (Putvinski et al 1997;Boozer 2015Boozer , 2017. The Dreicer generation (Connor & Hastie 1975), hot tails (Smith & Verwichte 2008;Zeng et al 2017) and avalanche mechanisms (Jayakumar, Fleischmann & Zweben 1993; are three main runaway generation processes. The Dreicer mechanism plays a major role when the collisional drag force on an energetic electron is less than the driving force by the toroidal electric field.…”
Section: Runaway Modementioning
confidence: 99%
“…2013) and in J-TEXT (Zeng et al. 2017). Kinetic instabilities driven by the runaways themselves can also induce local magnetic perturbations increasing the radial transport.…”
Section: Introductionmentioning
confidence: 99%